Cognition, quality of life and physical activity at the University of the Third Age: a systematic review (Research, Society and Development, 2020)
Objective: Investigate the longitudinal studies that approach the variables cognition, quality of life and physical activity in the elderly population of the Universities of the Third Age. Methodology: Systematic review, with searches in eleven electronic databases: BVS, PUBMED, PERIÓDICOS CAPES, WEB OF SCIENCE, EBESCO, PSYINFO, SCIELO, ERIC, REDALYC, LILACS e SCIENCE DIRECT. Results: From a total of 1403 articles found, the final review composition consisted of 14 articles that answered the inclusion and exclusion criterion. Final Considerations: It was found that the academic production around the UNATI environment still needs longitudinal studies, since only one study of this type verified the variables QoL, cognition and PA together in this population. It was possible to identify the benefit of PA for QoL, and the contradiction of the literature in the relationship of PA with cognition. As a limitation, the temporal cut is observed, as it is possible that some study on the theme outside the stipulated period was not included in this review.